(untitled) (South East Asia Journal of Public Health, 2016)
Hypertension is one of the leading risk factors for global mortality. A community based cross sectional descriptive study was conducted in Hmawbi Cantonment Area, Yangon Region in November, 2015. This study aimed to identify the prevalence, awareness and risk factors of hypertension concerning smoking, alcohol dinking, eating food pattern, taking regular exercise, stressful condition and body mass index (BMI). The sample consisted of 210 respondents from three Units (Light Infantry Regiments) were randomly selected to participate in the study. A pre-tested structured questionnaire was used as a data collection tool. It was found that 33.3% of respondents had hypertension; 55.7% achieved good awareness on hypertension as well; 16.7% respondents were current smoker; 7.6% had the history of alcohol drinking; 67.1% respondents took regular exercise; 29.5% respondents were in stressful condition; 32.9% re-spondents were overweight and 19.5% were obese. Hypertension was significantly associated with age (p-0.001), family income (p<0.001), awareness level (p-0.01), current smoking status (p<0.001), alcohol drinking (p<0.001), regular exercise taking (p<0.001), stressful condition (p<0.001), and increase BMI (p<0.001) of respondents. This setting in Hmawbi evidenced that age, family income, smoking, alcohol drinking, consumption of salty and fast food, stressful condition and increase BMI were identified as risk factors and taking regular exercise was protective. Over-all, over 50% of respondents having good awareness show that favorable circumstances exist for further strengthening the hypertension prevention and control program. These findings have implications for future public health interven-tion and clinical efforts to decrease the prevalence of hypertension among population. South East Asia Journal of Public Health Vol.6(1) 2016: 20-26